Effect of Cessna 172S Aircraft Engine Vibration on the ground on Aviator Academy Pilots - Hadi Prayitno; Dimas Endrawan Putra; M. Khoirul Anam; Wisnu Kuncoro; M. Nur Cahyo Hidayat (PT Inovasi Pratama Internasional, 2023)
There are various problems experienced by cadets at the Indonesian Aviator Academy (API) Banyuwangi, one of which is the effect of engine vibrations on the pilot of the cessna 172s aircraft. Vibration is a physical factor in the workplace that comes from the work equipment used. The impact of vibration on humans mainly occurs in certain parts of organs such as: chest, head, jaw, nerves and other joints. In general, exposure to mechanical vibrations in the body can cause disturbances in comfort at work, accelerate the occurrence of work fatigue and the emergence of disturbances to occupational health. The discomfort that affects the cadets at the Indonesian Aviator Academy (API) Banyuwangi affects the causes of fatigue that can cause plane crashes. This study aims to determine the effect of engine vibration on the performance of the pilot of the cessna 172s aircraft. The results of this study were based on questionnaire data obtained from cadets, 50% of 25 respondents answered that they had felt numbness in the hands when holding the steering lever of the aircraft and felt anxious when there was excessive vibration. The condition experienced can be a safety risk for pilots and cadets if the existing problem is not quickly given a solution to the solution.